HIV/AIDS Health Literacy in Zimbabwe - Terry, P. E.; Masvaure, T. B.; Gavin, L. (Methods of Information in Medicine, 2005)
Objective: This qualitative study was designed to assess program needs and evaluate and improve HIV/AIDS prevention efforts at the University of Zimbabwe.Methods: We conducted eight focus group discussions with 70 students and conducted key informant interviews with formal and informal opinion leaders. Four mixed-sex focus group discussions, two all-female, and two all-male sessions were held.Results: We found a pervasive sense of despondency and powerlessness among students. Consistent across focus groups, but particularly within the women’s groups, respondents revealed that financial and accommodation needs and peer pressure were causing many male and female students to engage in prostitution. Focus group discussions also revealed condom use with regular partners is low and that students dating partners who are employed find it hard to insist on condom use in the relationship.Conclusions: Participants stated programs had positively influenced their reduction in the number of sexual partners and intentions to get tested for HIV.
Keywords: HIV/AIDS; prevention; peer education; gender; edutainment